2002
DOI: 10.1021/bi026129y
|View full text |Cite
|
Sign up to set email alerts
|

Locally Disordered Conformer of the Hamster Prion Protein:  A Crucial Intermediate to PrPSc?

Abstract: A crucial step for transformation of the normal cellular isoform of the prion protein (PrP(C)) to the infectious prion protein (PrP(Sc)) is thought to entail a previously uncharacterized intermediate conformer, PrP*, which interacts with a template PrP(Sc) molecule in the conversion process. By carrying out (15)N-(1)H two-dimensional NMR measurements under variable pressure on Syrian hamster prion protein rPrP(90-231), we found a metastable conformer of PrP(C) coexisting at a population of approximately 1% at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
149
2
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 158 publications
(175 citation statements)
references
References 30 publications
22
149
2
2
Order By: Relevance
“…Furthermore, we note that the experimentally determined partial molar volume of ubiquitin decreases in the order of the decreasing conformational order, namely N 1 Ͼ N 2 Ͼ I Ͼ U. Along with the similar trend in other globular proteins (17)(18)(19)(20), the result clearly supports the volume theorem of protein, which can be stated as ''partial molar volume of a protein decreases in parallel with the decrease of its conformational order'' (8).…”
Section: Resultssupporting
confidence: 79%
“…Furthermore, we note that the experimentally determined partial molar volume of ubiquitin decreases in the order of the decreasing conformational order, namely N 1 Ͼ N 2 Ͼ I Ͼ U. Along with the similar trend in other globular proteins (17)(18)(19)(20), the result clearly supports the volume theorem of protein, which can be stated as ''partial molar volume of a protein decreases in parallel with the decrease of its conformational order'' (8).…”
Section: Resultssupporting
confidence: 79%
“…Perhaps contradictory to the modeling based on 2D crystals, 46 these studies suggest that a largely intact helix B and C is unlikely. Indeed, the NMR studies suggest that helix A actually has slightly more stability than helix B or C. 32,53 Recent amide protection studies of prion fibrils (PrP Sc rather than PrP C ) have indicated that a relatively short stretch of the sequence constitutes the b-sheet rich core of PrP Sc between residues 169 and 214, 24 again supporting the assertion that helix B and C are not retained as helices in the PrP* precursor to the scrapie isoform.…”
Section: Prp C Folding Intermediates and Stabilitymentioning
confidence: 91%
“…Studies using hydrostatic pressure 53 have been used to study the unfolding of PrP C in an attempt to identify folding intermediates. These folding intermediates may represent conformations of the prion protein (PrP*) on a pathway to PrP Sc and amyloid formation.…”
Section: Prp C Folding Intermediates and Stabilitymentioning
confidence: 99%
“…Recently, a metastable state of the PrP C was characterized by using a high-pressure NMR (14), where hydrostatic pressure was elevated up to 2,500 bar in an on-line high-pressure NMR cell. The thermodynamical stability profile shows that diverse residues in helices B and C are less stable, indicating the formation of the intermediate conformation (PrP*) (14).…”
mentioning
confidence: 99%